Reflections on the Brazilian urbanization: the case of Vitória da Conquista (BA): Reflexões sobre a urbanização brasileira: o caso de Vitória da Conquista (BA) (Revista de História da UEG (REVHIST), 2023)
This article aims to analyze the urbanization of the municipality of Vitória da Conquista (BA). For this, a qualitative methodology was used, especially based on a bibliographic review. A survey of a theoretical basis on Brazilian urbanization was carried out, in order to have a broader view on this theme and, concomitantly, to obtain better notes about this process in Vitória da Conquista. Through this study, it was possible to understand the dynamics that constitute the socio-spatial environment, which, under the capitalist aegis, (re)produces an unequal space.Keywords: Urbanization brazilian. Vitória da Conquista. Capitalism.